2000
DOI: 10.1080/10715760000300691
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress after moderate to extensive burning in humans

Abstract: Lipid peroxidation products, lipid antioxidants, and hematologic and blood chemistry changes were evaluated in plasma of patients after acute burning injury involving 10% (n=8), 20% (n=8), and 40% (n=5) of total body surface area (TBSA), 24 h after burning (baseline) up to 30 days after. Markedly increased plasma levels of malondialdehyde (MDA) were observed at baseline in all patients, according to the extent of the injury, then the values declined progressively. However, levels of MDA remained above normal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 32 publications
3
18
1
3
Order By: Relevance
“…Evidence from animal and human studies suggested that there is a correlation between the tissue MDA levels and the degree of burn complications, including shock and remote organ damage (32)(33)(34)(35). In the present study, burn-induced increase in the lung MDA levels were prevented by etanercept treatment, suggesting that antagonism of TNF- exerts a potent protective effect against lipid peroxidation.…”
Section: Discussionsupporting
confidence: 60%
“…Evidence from animal and human studies suggested that there is a correlation between the tissue MDA levels and the degree of burn complications, including shock and remote organ damage (32)(33)(34)(35). In the present study, burn-induced increase in the lung MDA levels were prevented by etanercept treatment, suggesting that antagonism of TNF- exerts a potent protective effect against lipid peroxidation.…”
Section: Discussionsupporting
confidence: 60%
“…A literatura tem sugerido que os oxidantes gerados contribuem para danos locais adicionais contribuindo na formação do edema. A ativação do sistema complemento, por sua vez, resultaria na inflamação de órgãos à distância 13,14 . Também a defesa antioxidante estaria enfraquecida nesse contexto 15 .…”
Section: Q U E I M a D U R A E E S T R E S S E O X I D A T I V Ounclassified
“…Uma diminuição de antioxidantes lipídicos (α-tocoferol, β-caroteno, vitamina A) e aumento da peroxidação lipídica também foram observados durante 30 dias em pacientes queimados, mesmo nos que exibiam apenas 10% de superfície corporal queimada 14 .…”
Section: Q U E I M a D U R A E E S T R E S S E O X I D A T I V Ounclassified
“…There is evidence of both local and systemic oxidant changes manifested by increased free radical activity and lipid peroxidation [4,14]. At the same time, a burn injury causes a remarkable reduction of total antioxidant status and scavenging capacity.…”
Section: Oxidative Stress In the Pathogenesis Of Liver Injury And Melmentioning
confidence: 99%
“…Clinical investigations show that burn-induced hepatic injury is accompanied by impairment of hepatic parenchymal cell function [14,68]. Plasma levels of aminotransferases such as AST and ALT, as indicators of hepatic injury and functional disorders, are higher after burns [44].…”
Section: Burn-induced Hepatic Morphological and Functional Changes Inmentioning
confidence: 99%